2004
DOI: 10.1111/j.1447-0756.2003.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide administration enhances hypoxic‐ischemic brain damage in newborn rats

Abstract: LPS potentiates hypoxic-ischemic insult in a dose-dependent fashion to cause brain damage in neonatal rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
42
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 27 publications
9
42
0
Order By: Relevance
“…inflammatory and apoptotic response could help to explain the primary sensitizing effect of LPS found in the immature brain in vivo (6,(21)(22)(23).We also found that LPS sensitized the immature brain if given 72 h before HI either at PND 4 or PND 7. This is interesting in that the animals have completely recovered from the systemic effects of LPS after 3 d. Early physiologic changes found after LPS injection, related to blood glucose, heart rate, temperature, and behavior, returned to normal after 3 d (24 -26).…”
supporting
confidence: 64%
“…inflammatory and apoptotic response could help to explain the primary sensitizing effect of LPS found in the immature brain in vivo (6,(21)(22)(23).We also found that LPS sensitized the immature brain if given 72 h before HI either at PND 4 or PND 7. This is interesting in that the animals have completely recovered from the systemic effects of LPS after 3 d. Early physiologic changes found after LPS injection, related to blood glucose, heart rate, temperature, and behavior, returned to normal after 3 d (24 -26).…”
supporting
confidence: 64%
“…[3][4][5] This synergistic effect was also reproduced in mammalian and avian animal models, combining HI insult and the lipopolysaccharide break-down product of bacteria in HI animal models. [6][7][8][9][10] However, the molecular mediators of this endotoxin effect in vivo are currently still unknown.…”
mentioning
confidence: 99%
“…The combined exposure to perinatal inflammation and neonatal HI results in a complex interplay of various signaling pathways of which the exact underlying mechanism has not been elucidated yet. Experimental peripheral inflammation induced by LPS is known to induce an inflammatory cerebral state leading to sensitization of the brain to HI injury [15,16,19,21,36,37]. Possible mechanisms via which peripheral LPS can sensitize the brain have been described extensively and consist of: (i) stimulation of endothelial cells of the blood-brain barrier (BBB), (ii) activation/priming of microglia via immune signals produced by endothelial and choroid plexus cells at the level of the BBB, (iii) direct transport of peripheral inflammatory molecules across the BBB, (iv) increased permeability of the BBB, which enhances the influx of peripheral immune cells into the brain, (v) stimulation of the vagal nerve by peripheral cytokines leading to signaling in the brain and (vi) the effects of inflammation on G-protein-coupled receptor signaling in the brain [17,38,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The general view is that inflammation before HI sensitizes the brain and thereby aggravates HI cerebral injury. However, the exact mechanisms underlying proinflammatory sensitization are still unclear [15,16,17,18,19,20,21]. To date, the exact timing of the sensitizing effect of LPS on the intensity of cerebral gray and white matter injury and the formation of an acellular cyst after HI have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%